Transaksi Belanja Online di Masa Pandemi melalui Aplikasi Shopee Paylater Perspektif Imam Asy-Syafi’i dan Ibnu Qudamah Studi Kasus Kecamatan Datuk Bandar Timur Kota Tanjungbalai - Nely, Seprida (ARZUSIN, 2023)
The government's appeal to the public to stay at home during the Covid-19 pandemic has resulted in many people choosing to buy all goods online to avoid direct contactIn additiongoods sold online are more affordable than prices in offline stores and make it easier for buyers because they don't have to go to the store directlyOne such online shopping platform is ShopeeThe purpose of this study is to examine more deeply about online shopping transactions during a pandemic through the Shopee Paylater application from the perspective of Imam Ssy-Syafi'l and Ibnu Qudamah (a case study of Datuk Bandar Timur district, Tanjung Balai City) and how important it is to understand the features available on the platform. online shopping in order to frame the risks that might occur. This study used a qualitative method with an empirical juridical approach and data collection techniques used were interviews and literature study. In this study it can be seen that buying and selling online through the Shopee Paylater Platform is a transaction that contains debtsThe case of using the Shopee Paylater application in Datuk Bandar Timur District found 4 people who according to them the shopping system with a loan from Shopee made their shopping activities run when they didn't have money, and was considered effectiveImam Asy-Syafi'i allows Shopee PaylaterWhereas Ibnu Qudamah's opinion states that transactions through Shopee Paylater include transactions that contain elements of usury in them, therefore the law is haramHowever, the strongest opinion between Imam Shafi'i and Ibn Qudamah is that of Imam Ash-Shafi'i. Because Imam Asy-Shafi'i used a special argument while Ibn Qudamah used a general argument.